The role of ideas in Turkish foreign policy: The JDP-Davutoğlu paradigm and its role after 2002 - Yorulmazlar, Emirhan. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2015., 2015)
This dissertation posits that ideas had a role in explaining change in Turkish foreign policy during the Justice and Development Party (JDP) era. It is argued this ideational change not only altered policy goals and instruments, but also the nature of Turkish foreign policy as a whole. The assumption is that the political flux and the government’s political choice gave leeway to Davutoğlu’s ideas to embody the emergent JDP- Davutoğlu paradigm. A twofold theoretical framework is applied first to extract the role of ideas, second to depict the paradigmatic change. To that end, the dissertation brings in the traditional bureaucratic paradigm as a null hypothesis, which has survived the post-Cold War era through a laborious process of adjustment and overcoming anomalies under bureaucratic stewardship. Early on, the JDP developed a dual approach in foreign policy, embracing status quo and change at the same time. This was seen both as a secure and expedient way to build a power base for the incumbent government. The JDP’s early term accommodationist approach went hand-in-hand with an urgent need for new ideas to realize its self-declared transformative agenda. Davutoğlu’s ideas supplied this demand, which later on laid the groundwork for a gradual paradigmatic shift. The emerging paradigm got steam under the JDP’s political aegis. When Davutoğlu was appointed as the Minister of Foreign Affairs, the JDP-Davutoğlu paradigm has already been operative. His appointment essentially pointed to a move towards its institutionalization. Yet this was not merely a “Davutoğlu affair.” It also reflected political, bureaucratic and institutional changes within the Turkish polity. Despite growing anomalies, the overall response of Turkish foreign policy to the regional upheaval after 2011 has been shaped by adjustments within the parameters of the evolving paradigm.
Keywords: Turkey -- Foreign relations -- 21st century.